2023
DOI: 10.1186/s13293-023-00510-1
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of uric acid and sex on cognition and psychiatric symptoms in asymmetric Parkinson’s disease

Abstract: Background Non-motor symptoms are an important early feature of Parkinson’s disease (PD), encompassing a variety of cognitive and psychiatric symptoms that seem to manifest differently depending on motor symptom asymmetry. Different factors, such as uric acid (UA) and sex, seem to influence cognitive and psychiatric expression in PD, however their interplay remains to be better understood. Methods Participants taking part in the Parkinson’s Progres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The SUA level has a “J” shaped relationship with the risk of death associated with prostate cancer with the risk of death decreasing and then increasing as SUA levels rise. High levels of SUA are protective against neurological disorders, such as Parkinson’s disease, whereas low levels are harmful. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SUA level has a “J” shaped relationship with the risk of death associated with prostate cancer with the risk of death decreasing and then increasing as SUA levels rise. High levels of SUA are protective against neurological disorders, such as Parkinson’s disease, whereas low levels are harmful. …”
Section: Discussionmentioning
confidence: 99%
“… 18 Moreover, at physiological concentrations, uric acid acts as an antioxidant, 19 23 scavenging oxygen radicals and exerting a protective effect on most organs, 19 , 22 except the nervous system. 22 Several studies have shown that low uric acid levels damage the nervous system, 24 , 25 whereas high uric acid levels exert protective effects. 26 Many studies have suggested that high-fat diets cause elevated uric acid levels in addition to elevated blood lipids.…”
Section: Introductionmentioning
confidence: 99%